1998
DOI: 10.1046/j.1365-3040.1998.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

The nopaline synthase (nos) promoter is inducible by UV‐B radiation through a pathway dependent on reactive oxygen species

Abstract: The molecular mechanism of plant response to UV-B radiation was studied using the nopaline synthase (nos) promoter, which has been shown to be inducible by methyl jasmonate (MJ) and reactive oxygen species (ROS). In the leaves of transgenic tobacco (Nicotiana tabacum L.) plants that carried a fusion between the nos promoter and the chloramphenicol acetyltransferase (cat) gene, 2 h of UV-B treatment resulted in a transient increase in the level of cat mRNA, a maximum being reached at 6 h after the UV-B treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…As to the question whether oxidative stress and oxidative damage acted as the mediator and caused the adaptation response, some work has been done to clarify the genetic regulation by ROS or the products of oxidative damage under stressing conditions. First of all, it has been found that the response of plants to biotic and abiotic stresses including UV‐B stress is often mediated by several rapid genetic processes that are associated with the formation of ROS and the induction of oxidative damage to lipids, proteins and DNA molecules (10,15,42,43). In addition, however, H 2 O 2 , O 2 ·− and lipid hydroperoxides are considered to be suitable signaling species for initiating functional modulation without disruption of cellular integrity, which allows the organisms to adapt to the stress conditions (44).…”
Section: Discussionmentioning
confidence: 99%
“…As to the question whether oxidative stress and oxidative damage acted as the mediator and caused the adaptation response, some work has been done to clarify the genetic regulation by ROS or the products of oxidative damage under stressing conditions. First of all, it has been found that the response of plants to biotic and abiotic stresses including UV‐B stress is often mediated by several rapid genetic processes that are associated with the formation of ROS and the induction of oxidative damage to lipids, proteins and DNA molecules (10,15,42,43). In addition, however, H 2 O 2 , O 2 ·− and lipid hydroperoxides are considered to be suitable signaling species for initiating functional modulation without disruption of cellular integrity, which allows the organisms to adapt to the stress conditions (44).…”
Section: Discussionmentioning
confidence: 99%
“…In plant cells, it has been increasingly suggested that reactive oxygen species (ROS) could mediate many aspects of cellular signaling (Price et al 1994;Ingram and Bartels 1996;Yamaguchi-Shinozaki 1996, 1997;Yu et al 1998;Hippeli et al 1999;Zhang et al 2001;Zhao et al 2001;Rental and Knight 2004). We have widely probed the water deficit-induced ABA accumulation in relation to various signaling pathways, such as the Ca 2+ , calmodulin (CaM), and CDPKs pathways, the inositol 1,4,5-trisphosphate/diacylglycerol pathway, the Ser/Thr reversible phosphorylation pathway and the mitogenactivated protein kinase pathway.…”
mentioning
confidence: 99%